2020
DOI: 10.1007/s11270-020-04692-x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Functions of Epilithic Riverine Biofilms

Abstract: This article relates epilithic dry- and wet-seasonal bacterial biofilm composition to water quality along Río de la Sabana near Acapulco, Mexico. Samples were taken from various locations including nearly pristine upland locations, adjacent to residential floodplain developments, and immediately upstream from an estuarine lagoon. Bacterial composition was identified through sequential DNA analysis at the phylum, class, order, and family levels, with most of these categorized as heterotrophs, autotrophs, denitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
1
2
1
Order By: Relevance
“…These results contrast with those of two previous studies, in which significant differences were observed between sampling sites [81,85] but not between sampling dates [81], which suggests that the composition of the microbial community is relatively stable over time but may vary according to the characteristics of each sampling site [81,84]. Other studies have also shown that the composition of phyla within biofilms can be influenced by pollution, seasonal variations and the physico-chemical properties of the water [54,64,76,86]. These observations highlight the sensitivity of biofilm communities not only to geographical location, and thus the environment, but also to time, particularly seasons [82,84,87].…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…These results contrast with those of two previous studies, in which significant differences were observed between sampling sites [81,85] but not between sampling dates [81], which suggests that the composition of the microbial community is relatively stable over time but may vary according to the characteristics of each sampling site [81,84]. Other studies have also shown that the composition of phyla within biofilms can be influenced by pollution, seasonal variations and the physico-chemical properties of the water [54,64,76,86]. These observations highlight the sensitivity of biofilm communities not only to geographical location, and thus the environment, but also to time, particularly seasons [82,84,87].…”
Section: Discussioncontrasting
confidence: 94%
“…An analysis of the biofilm microbiome characteristics from three freshwater sites showed that the predominant bacterial phyla at our study sites were Proteobacteria, Bacteriodetes, Planctomycetes, and Cyanobacteria, as reported in previous studies but with different abundances [50][51][52][53][54][55]. The predominance of Proteobacteria was highlighted in previous studies investigating surface waters [56][57][58][59][60][61] and biofilms from various environments [51,62,63] through 16S rRNA gene analysis.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, we are not aware of any study that investigated the specific effect of wastewater microorganisms on this phylum. Deinococcaceae have already been associated to periphyton growing in reference (unpolluted) sites in a previous study comparing community composition along an urban pollution gradient in a stream (Pineda-Mora et al, 2020), indicating their potential sensitivity to wastewater constituents. The presence of Methylobacteriaceae and Microbacteriaceae in the Group Negative may be explained by their association with microalgae (Levy et al, 2009;Paddock et al, 2020), which seemed to be negatively impacted by wastewater microorganisms in terms of abundance (i.e.…”
Section: Identification Of Periphyton Taxa Impacted By Wastewater Mic...mentioning
confidence: 88%